Tuning the hybridization and charge polarization in metal nanoparticles dispersed over Schiff base functionalized SBA-15 enhances CO2 capture and conversion to formic acid - Cherevotan, Arjun; Ray, Bitan; Yadav, Anish; Bagchi, Debabrata; Singh, Ashutosh Kumar; Riyaz, Mohd; Churipard, Sathyapal R.; Naral, Vinay; Kaur, Komalpreet; Gautam, Ujjal K.; Vinod, Chathakudath P.; Peter, Sebastian C. (Journal of Materials Chemistry A, 2022)
Different Schiff base functionalized SBA-15 materials were synthesized through condensation reactions between 3-aminopropyltriethoxysilane (APTES) and different aldehydes (glutaraldehyde and butyraldehyde) over a mesoporous silica, SBA-15 (APTES-GLU/SBA-15 and APTES-BUT/SBA-15). Both static and dynamic experiments have been used for testing the CO2 capture efficiency of these materials. The hybridization of the N atom in APTES has been tuned from sp(3) to sp(2) upon condensation facilitating optimum CO2 capture in the direct synthesis of APTES-GLU/SBA-15. The undesirable oxides of nitrogen have been removed during the synthesis process to improve the CO2 capture efficiency. These materials were employed as supports for Pd-Ag and Pd-Ni bimetallic systems for the selective conversion of the captured CO2 to formic acid (FA) in 0.5 M KHCO3 solution. The Pd-Ni catalyst system exhibited enhanced CO2 to FA conversion activity compared to other heterogeneous systems, which is similar to 4 times better than that of the Pd-Ag system in this study. The X-ray absorption studies over the catalyst material confirmed that the relatively electron-deficient Ni in Pd-Ni compared to Ag in Pd-Ag favoured higher charge polarization between the metals in the Pd-Ni system enhancing the CO2 to FA conversion. The experimental observations are well supported by the DFT calculations.